Optical tweezing using tunable optical lattices along a few-mode silicon waveguide. Issue 12 (18th May 2018) - Pin, C.; Jager, J.-B.; Tardif, M.; Picard, E.; Hadji, E.; de Fornel, F.; Cluzel, B.
Abstract : On-chip optical trapping and manipulation of beads and bacteria using near-field optical lattices in few modes silicon waveguide are demonstrated. Abstract : Fourteen years ago, optical lattices and holographic tweezers were considered as a revolution, allowing for trapping and manipulating multiple particles at the same time using laser light. Since then, near-field optical forces have aroused tremendous interest as they enable efficient trapping of a wide range of objects, from living cells to atoms, in integrated devices. Yet, handling at will multiple objects using a guided light beam remains a challenging task for current on-chip optical trapping techniques. We demonstrate here on-chip optical trapping of dielectric microbeads and bacteria using one-dimensional optical lattices created by near-field mode beating along a few-mode silicon nanophotonic waveguide. This approach allows not only for trapping large numbers of particles in periodic trap arrays with various geometries, but also for manipulating them via diverse transport and repositioning techniques. Near-field mode-beating optical lattices may be readily implemented in lab-on-a-chip devices, addressing numerous scientific fields ranging from bio-analysis to nanoparticle processing.